Counsellor-in-Residence: Evaluation of a Residence-Based Initiative to Promote Student Mental Health - Beks, Tiffany Anne; Cairns, Sharon L; Smygwaty, Serena; Miranda Osorio, Olga A.L.; Hill, Sheldon J (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2018)
Many universities have implemented campus-based initiatives addressing students’ mental health with the goal of promoting well-being. One such initiative is the newly developed Counsellor-in-Residence (CIR) program at the University of Calgary, which targets students’ mental health by providing residence-based counselling services and mental health programming. In this process evaluation, students completed three waves of data collection conducted over the academic year. Each wave measured students’ mental health literacy, using the Mental Health Literacy Scale (O’Connor & Casey, 2015), and resiliency, using the Connor-Davidson Resilience Scale-25 (Connor & Davidson, 2003). Males reported lower mental health literacy than females (p < .001), and international students reported lower mental health literacy than domestic students (p < .001). No differences in resilience levels were found between groups. These findings suggest that male and international students experience additional barriers to accessing campus-based mental health services. Implications for residence-based mental health programming that target male and international students are discussed.